Transformation of temporal sequences in the zebra finch auditory system - Lim, Yoonseob; Lagoy, Ryan; Shinn-Cunningham, Barbara G.; Gardner, Timothy J. (ELIFE SCIENCES PUBLICATIONS LTD, 2016)
This study examines how temporally patterned stimuli are transformed as they propagate from primary to secondary zones in the thalamorecipient auditory pallium in zebra finches. Using a new class of synthetic click stimuli, we find a robust mapping from temporal sequences in the primary zone to distinct population vectors in secondary auditory areas. We tested whether songbirds could discriminate synthetic click sequences in an operant setup and found that a robust behavioral discrimination is present for click sequences composed of intervals ranging from 11 ms to 40 ms, but breaks down for stimuli composed of longer inter-click intervals. This work suggests that the analog of the songbird auditory cortex transforms temporal patterns to sequence-selective population responses or spatial codes', and that these distinct population responses contribute to behavioral discrimination of temporally complex sounds.
Keywords: TAENIOPYGIA-GUTTATA; TONOTOPIC ORGANIZATION; SONG-DISCRIMINATION; TAENOPYGIA-GUTTATA; CONSPECIFIC SONG; LEARNED SONG; AVIAN BRAIN; FIELD-L; FOREBRAIN; SONGBIRDS